PEMODELAN DAN ANALISA STRUKTUR BAWAH PERMUKAAN DAERAH PROSPEK PANASBUMI KEPAHIANG BERDASARKAN METODE GAYABERAT - Roy Bryanson Sihombing; Rustadi Rustadi (Engineering Faculty Universitas Lampung, 2018)
Research has been conducted in Kepahiang area using gravity data with the aim of identify faults based on analysis of the Second Vertical Derivative (SVD) and interpreting structure sub-surface of the based on 3D inverse modelling from Bouguer anomaly and residual anomaly. The research area have an Bouguer anomaly between 38 mGal - 74 mGal, where the high Bouguer anomaly value has a value range of 63,2 mGal - 74 mGal located in the southwest direction of the research area. Whereas the low Bouguer anomaly value has a range of values 38 mGal - 47 mGal located in the north of the research area. To know the existence of fault structure in research area, conducted filtering Second Vertical Derivative (SVD) on the map Bouguer anomaly, regional and residual. The structure faulting is shown with contour of zero and between the contours of high and low. From the analysis of SVD complete anomaly Bouguer and SVD residual anomaly there are 8 (eight) faulting, while from SVD regional anomaly there are 4 (four) fault. 3D inversion modeling of the residual anomaly was done to prove the existence of the fault analyzed based on filtering Second Vertical Derivative (SVD). Based on the results of inversion 3D residual anomaly been gained one (1) reservoir in a northern direction research area and two (2) in the direction of west the research area by a contrast the density of -0,0719356 gr/cc until -0,236053 gr/cc with a depth of 0 meters up to 4.705 meters.